Study of Shigella flexneri via traditional-bacterial isolation, PCR-sequencing identification, and phylogenetic tree analysis in Al-Diwaniyah City, Iraq - Alaa Abdelkadhim Jawad (Al-Qadisiyah Journal of Pure Science, 2019)
The current study intended to isolate and identify Shigella flexneri via traditional bacterial isolation (TBI), PCR-sequencing identification (PSI), and phylogenetic tree analysis(PTA) from patients attended Al-Diwaniyah General Teaching Hospital, Al-Diwaniyah City, Iraq. A total of  25 stool samples were collected and subjected to the above mentioned techniques. The results of the TBI revealed the presence of S. flexneri in these samples. The PCR results confirmed the identification of these bacteria in these samples after a piece, 1256 bp, of the gyrB gene, encodes the subunit B protein of DNA gyrase, was targeted. For the sequencing of 2 samples, the results showed the complete confirmation revealing the correctness of the TBI and the PCR results in identifying these bacteria in the tested samples. The PTA revealed separate distinctive clustering of the sequenced samples in one branch of the phylogenetic tree. The current study enhances the documentation that S. flexneri is one of the infectious agents that causes GIT-related infections in the current tested city.